Investigating oral nicotine pouch use among adults in Riyadh, Saudi Arabia: prevalence, awareness, susceptibility, and associated symptoms - Alkharaan, Hassan; Alrubayyi, Abdulaziz; Kariri, Majed; Alasqah, Mohammed; Alnufaiy, Banna; Alzahrani, Hanadi G.; Gufran, Khalid; Altkhais, Yasser; Algharbi, Muteb; Alarfaj, Fahad (Frontiers in Public Health, 2025)
BackgroundOral nicotine pouches (ONPs) have rapidly gained popularity as a novel nicotine delivery method. However, data on ONP use, awareness, and associated beliefs in Saudi Arabia remain limited. This study aimed to investigate these aspects among adults in Riyadh region.MethodsA cross-sectional survey was conducted in 2024 involving 831 Saudi adults (age ≥ 18 years). Participants completed a self-administered questionnaire assessing ONP awareness, prevalence, beliefs, and susceptibility as well as potential associated ONP use symptoms. Logistic and multinomial regression models were employed to analyze the associations between these variables.ResultsOverall, 59.3% of participants reported awareness of ONPs, and 14.2% having used them. Males were more aware (ORadj = 1.97, p < 0.0001) and user (ORadj = 2.86, p = 0.03) of ONP than females. Similarly, younger adults (aged 18–29 and 30–39 years) demonstrated higher ONP awareness (ORadj = 4.67 and 4.88, respectively, both p < 0.0001) and use (ORadj = 6.91, p < 0.002 and 6.12, p < 0.003, respectively) compared to older adults (40–69 years). Additionally, 95.8% of ONP users were smokers, more likely to be cigarette (ORadj = 9.53, p < 0.0001) or e-cigarette (ORadj = 8.43, p < 0.0001) smokers. Approximately 60% of participants demonstrated susceptibility to ONP use, characterized by curiosity, limited knowledge of health risks, and potential willingness to use. Favorable beliefs about ONPs were more prevalent among users. Furthermore, a positive correlation was observed between the frequency of ONP use and the likelihood of experiencing associated symptom (r = 0.3, p = 0.0009), with abdominal symptoms being the most reported symptom.ConclusionGiven that 95.8% of ONP users in this study were smokers, these findings suggest a potential future role for ONPs as a harm reduction strategy within the context of smoking cessation in Saudi population in Riyadh. However, continuous surveillance and targeted public health interventions are crucial to mitigate the potential negative consequences associated with ONP use.